Developing assessment instruments for the sensory acceptability of food products - Sugiyono Sugiyono; Djemari Mardapi; I Gusti Putu Suryadarma (Universitas Negeri Yogyakarta, 2017)
The study investigated the constructs and characteristics of physiological, psychological, and sensory instruments. The data were collected by means of a questionnaire, physiological instrument, psychological instrument, and sensory instrument. The expert judgment conclusions were calculated by means of Aiken formula; the instrument construct validity was analyzed with confirmatory factor analysis by the goodness-of-fit test at the significance level of 0.05; the reliability estimate by generalizability with a G-study coefficient ≥ 0.7 and an ICC coefficient ≥ 0.7; and the instrument characteristics were analyzed by D-study. The results of the study are as follows: (1) the physiological instrument consisted of nine constructs: four constructs of psychological instrument and  five constructs of sensory instrument; (2) three instruments had good face validity, content validity and construct validity, supported by the empirical evidence at p > 0.05; (3) the reliability estimate of the three instruments was good and the reliability estimate was supported by empirical evidence with G coefficients of > 0.7 and ICC coefficients of > 0.7, (4) the three instruments had characteristics that might be appropriate to be used by the university students of culinary program and the vocational high school students of culinary program.